Axillary lymph node dissection versus radiotherapy in breast cancer with positive sentinel nodes after neoadjuvant therapy (ADARNAT trial) - Garcia-Tejedor, Amparo; Ortega-Exposito, Carlos; Salinas, Sira; Luzardo-González, Ana; Falo, Catalina; Martinez-Pérez, Evelyn; Pérez-Montero, Héctor; Soler-Monsó, M. Teresa; Bajen, Maria-Teresa; Benitez, Ana; Ortega, Raul; Petit, Anna; et al. (Frontiers in Oncology, 2023)
Breast cancer surgery currently focuses on de-escalating treatment without compromising patient survival. Axillary radiotherapy (ART) now replaces axillary lymph node dissection (ALND) in patients with limited sentinel lymph node (SLN) involvement during the primary surgery, and this has significantly reduced the incidence of lymphedema without worsening the prognosis. However, patients treated with neoadjuvant systemic treatment (NST) cannot benefit from this option despite the low incidence of residual disease in the armpit in most cases. Data regarding the use of radiotherapy instead of ALND in this population are lacking. This study will assess whether ART is non-inferior to ALND in terms of recurrence and overall survival in patients with positive SLN after NST, including whether it reduces surgeryrelated adverse effects.This multicenter, randomized, open-label, phase 3 trial will enroll 1660 patients with breast cancer and positive SLNs following NST in approximately 50 Spanish centers over 3 years. Patients will be stratified by NST regimen and nodal involvement (isolated tumoral cells or micrometastasis versus macrometastasis) and randomly assigned 1:1 to ART without ALND (study arm) or ALND alone (control arm). Level 3 and supraclavicular radiotherapy will be added in both arms. The primary outcome is the 5-year axillary recurrence determined by clinical and radiological examination. The secondary outcomes include lymphedema or arm dysfunction, quality of life based (EORTC QLQ-C30 and QLQ-BR23 questionnaires), disease-free survival, and overall survival.